The Influence of Lifestyle and Fear of Missing Out on Repurchase Intention with Word of Mouth as Intervening in the Contemporary Beverage Industry - adelika, adelika; Rahma, Tri Inda Fadhila; Dharma, Budi (MEC-J (Management and Economics Journal), 2024)
This study aims to determine the lifestyle and fear of missing out on repurchase intention with word of mouth as intervening in the contemporary beverage industry. Research using a quantitative approach that is causal / associative research using primary data, namely questionnaires, which are distributed directly to consumers who are in the Sun Thai Tea Stabat. The research sample was taken using the Lemeshow formula because the population size was unknown and varied. The sample in this study is to use the error significance level 10% with the result of the minimum sample size 67 and rounded up to 100 samples. This research uses Structural Equation Modeling (SEM) analysis which is assisted by using SmartPLS 4.0 software. The results showed that lifestyle has a positive and significant effect on repurchase interest, lifestyle has a positive and significant effect on word of mouth, fear of missing out has a positive and significant effect on repurchase interest, fear of missing out has a positive and significant effect on word of mouth, repurchase interest has a positive and significant effect on word of mouth, lifestyle has an indirect positive and significant effect on repurchase interest through word of mouth, fear of missing out has no indirect impact on future purchases interest through word of mouth.